2015
DOI: 10.1177/0194599815580765
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis of Carbon Nanoparticles for Identifying Lymph Nodes and Protecting Parathyroid Glands during Surgery

Abstract: CNs partially improve the extent and accuracy of neck dissection and preserve the normal anatomic structure and physiologic function of the parathyroid glands during thyroid cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 13 publications
4
50
0
Order By: Relevance
“…Recently, the technology of carbon nanoparticles (CNs) has been applied to distinguish developing lymph nodes from nondeveloping parathyroid glands, which can facilitate preservation of the normal anatomic structure and physiologic function of parathyroid glands during thyroidectomy and central neck dissections. [10] However, frozen sections are still a necessity when encountering an atypical parathyroid. In this study, we excluded patients in which even a frozen section could not positively identify the gland.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the technology of carbon nanoparticles (CNs) has been applied to distinguish developing lymph nodes from nondeveloping parathyroid glands, which can facilitate preservation of the normal anatomic structure and physiologic function of parathyroid glands during thyroidectomy and central neck dissections. [10] However, frozen sections are still a necessity when encountering an atypical parathyroid. In this study, we excluded patients in which even a frozen section could not positively identify the gland.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that CNs could help visualize the lymph nodes and preserve the parathyroid. In addition, a meta-analysis has also been published to support this viewpoint 20. However, controversy still exists about the usefulness of CNs.…”
Section: Introductionmentioning
confidence: 99%
“…Before 2014, all articles published on the usage of CNs in thyroid cancer surgeries were in Chinese, and there were only limited randomized controlled trials (RCTs) reported. Accordingly, a considerable amount of non-RCTs were included in the previous meta-analysis 20. However, in recent years, more RCTs have been published.…”
Section: Introductionmentioning
confidence: 99%
“…The most important point for this comparison was parathyroid function recovery; although the total thyroidectomy group showed many parathyroidectomies, all of these removed parathyroids were confirmed by intraoperative frozen pathology and were autotransplanted in the sternocleidomastoid, with the surgical details presented in our previous research 25. Carbon nanoparticles as a lymph node tracer may help to identify affected lymph nodes and preserve the parathyroid 26,27…”
Section: Discussionmentioning
confidence: 99%